COX6A2 variants cause a muscle‐specific cytochrome c oxidase deficiency. Issue 2 (2nd July 2019) - Inoue, Michio; Uchino, Shumpei; Iida, Aritoshi; Noguchi, Satoru; Hayashi, Shinichiro; Takahashi, Tsutomu; Fujii, Katsunori; Komaki, Hirofumi; Takeshita, Eri; Nonaka, Ikuya; Okada, Yukinori; Yoshizawa, Takuya; et al.
Abstract : Objective: Cytochrome c oxidase (COX) deficiency is a major mitochondrial respiratory chain defect that has vast genetic and phenotypic heterogeneity. This study aims to identify novel causative genes of COX deficiency with only striated muscle–specific symptoms. Methods: Whole exome sequencing was performed in 2 unrelated individuals who were diagnosed with congenital myopathy and presented COX deficiency in muscle pathology. We assessed the COX6A2 variants using measurements of enzymatic activities and assembly of mitochondrial respiratory chain complexes in the samples from the patients and knockout mice. Results: Both patients presented muscle weakness and hypotonia in 4 limbs along with facial muscle weakness. One patient had cardiomyopathy. Neither patient exhibited involvement from other organs. Whole exome sequencing identified biallelic missense variants in COX6A2, which is expressed only in the skeletal muscle and heart. The variants detected were homozygous c.117C > A (p.Ser39Arg) and compound heterozygous c.117C > A (p.Ser39Arg) and c.127T > C (p.Cys43Arg). We found specific reductions in complex IV activities in the skeletal muscle of both individuals. Assembly of complex IV and its supercomplex formation were impaired in the muscle. Interpretation: This study indicates that biallelic variants in COX6A2 cause a striated muscle–specific form of COX deficiency. ANN NEUROL 2019;86:193–202